Benign Biliary Strictures: A Comprehensive Review - Ashat, Munish; Berei, Joseph; El-Abiad, Rami; Khashab, Mouen A. (Turkish Journal of Gastroenterology, 2024)
Abstract: Benign biliary strictures (BBS) ensue from inflammatory conditions (e.g., chronic pancreatitis) or post surgery (e.g., cholecystectomy and liver transplant). High-quality cross-sectional imaging studies such as computed tomography or magnetic resonance cholangiopancre atography are essential in the diagnosis and planning of therapeutic interventions and in ruling out malignancy. Endoscopic retrograde cholangiopancreatography with dilation and stenting is the mainstay treatment for BBS, while surgery is reserved for failed endoscopy or refractory cases. Cite this article as: Ashat M, Berei J, El-Abiad R, Khashab MA. Benign biliary strictures: A comprehensive review. Turk J Gastroenterol. 2024;35(7):513-522.